The revolution of software defined networking in terms of capability of network centralization compared to conventional approach / Nordiana Ghani - Ghani, Nordiana (2016)
This paper presents a development of simulator based on Software Defined Networking. The characteristic of Controller and the way it works is studied to see capability of SDN which promises to enable network technology innovation and adaptability while reducing complexity and administrative overhead. Wireshark is used as monitoring tools to oversee the packets traverse between Controller and Routing devices. Network Topology is created and dump command is executed to display the information of the connected network nodes. The pingall command is then executed to view the interconnection between Controller and Routing Devices. Thus, the function of SDN controller is now derived. As a result, managing of networks can be simplified using SDN Controller.